Latent Pulmonary Vascular Disease May Alter the Response to Therapeutic Atrial Shunt Device in Heart Failure. Issue 21 (31st March 2022) - Borlaug, Barry A.; Blair, John; Bergmann, Martin W.; Bugger, Heiko; Burkhoff, Dan; Bruch, Leonhard; Celermajer, David S.; Claggett, Brian; Cleland, John G.F.; Cutlip, Donald E.; Dauber, Ira; Eicher, Jean-Christophe; et al.
Abstract : Background: In REDUCE LAP-HF II (A Study to Evaluate the Corvia Medical, Inc IASD System II to Reduce Elevated Left Atrial Pressure in Patients With Heart Failure), implantation of an atrial shunt device did not provide overall clinical benefit for patients with heart failure with preserved or mildly reduced ejection fraction. However, prespecified analyses identified differences in response in subgroups defined by pulmonary artery systolic pressure during submaximal exercise, right atrial volume, and sex. Shunt implantation reduces left atrial pressures but increases pulmonary blood flow, which may be poorly tolerated in patients with pulmonary vascular disease (PVD). On the basis of these results, we hypothesized that patients with latent PVD, defined as elevated pulmonary vascular resistance during exercise, might be harmed by shunt implantation, and conversely that patients without PVD might benefit. Methods: REDUCE LAP-HF II enrolled 626 patients with heart failure, ejection fraction ≥40%, exercise pulmonary capillary wedge pressure ≥25 mm Hg, and resting pulmonary vascular resistance <3.5 Wood units who were randomized 1:1 to atrial shunt device or sham control. The primary outcome—a hierarchical composite of cardiovascular death, nonfatal ischemic stroke, recurrent HF events, and change in health status—was analyzed using the win ratio. Latent PVD was defined as pulmonary vascular resistance ≥1.74 Wood units (highest tertile) at peak exercise, measured before randomization. Results: Compared with patients without PVD (n=382), those with latent PVD (n=188) were older, had more atrial fibrillation and right heart dysfunction, and were more likely to have elevated left atrial pressure at rest. Shunt treatment was associated with worse outcomes in patients with PVD (win ratio, 0.60 [95% CI, 0.42, 0.86]; P =0.005) and signal of clinical benefit in patients without PVD (win ratio, 1.31 [95% CI, 1.02, 1.68]; P =0.038). Patients with larger right atrial volumes and men had worse outcomes with the device and both groups were more likely to have pacemakers, heart failure with mildly reduced ejection fraction, and increased left atrial volume. For patients without latent PVD or pacemaker (n=313; 50% of randomized patients), shunt treatment resulted in more robust signal of clinical benefit (win ratio, 1.51 [95% CI, 1.14, 2.00]; P =0.004). Conclusions: In patients with heart failure with preserved or mildly reduced ejection fraction, the presence of latent PVD uncovered by invasive hemodynamic exercise testing identifies patients who may worsen with atrial shunt therapy, whereas those without latent PVD may benefit.